Dukungan Keluarga Dengan Kepatuhan Minum Oat (Obat Anti Tuberkulosis) Pada Pasien Tuberkulosis Paru di Wilayah Kerja Puskesmas Tuban - Afifa, Sholihatun; Su’udi, Su’udi; Sumiatin, Titik (Peneliti.net, 2024)
Pulmonary Tuberculosis can be treated and cured quickly. Tuberculosis patients take medication continuously for 6 to 9 months to recover from pulmonary TB, however in Indonesia there are still cases of patients dropping out of medication for various reasons, one of which is a lack of family support regarding the treatment of TB patients. The aim is to find out the relationship between family support and adherence to taking OAT in pulmonary tuberculosis patients in the Tuban Community Health Center working area. Collaborative analytic research design with a cross-sectional approach. The study population was all pulmonary TB patients who were undergoing treatment in 2022 at the Tuban Community Health Center, a total of 61 people. The sampling technique used was total sampling. Independent variable is family support, dependent variable is adherence to taking OAT. The method of collecting data by distributing questionnaires was tested using the Spearman Rank Correlation test. The results showed that the majority (70.5%) of patients had good family support, and the majority had moderate medication adherence (60.7%). After carrying out the Spearman Rank Correlation test, it was obtained that p = 0.000 with p < 0.005, showing that there was a fairly strong significant relationship between family support and adherence to taking OAT (0.556). Family support is one of the factors that influences the fulfillment of medication in pulmonary tuberculosis patients. The higher the patient's family support, the higher the compliance with taking medication in pulmonary tuberculosis patients. Medication adherence is critical to preventing MDR and unsuccessful treatment courses.